Game-based forehand smash training model development for Indonesian badminton athlete - Kusnadi, N.; Asmawi, M.; Tangkudung, J. (Journal of Education, Health and Sport, 2019)
This study is aimed at developing training model for forehand smash skill in badminton. It applied Research and Development (R and D) and it adopted the method from Borg and Call featuring 10 steps to accomplish. To determine the level of significance of forehand smash skill, the study applied t-test. The data were calculated using t-test with a significance level of 0.05. The results show that the average value of pretest 18.74 and posttest average 21.00. To determine its significance level, this study compared t count and t value in the table. The result was t count = = -5.888, df = 41 and significance values = 0.00 <0.05. It means that there were significant differences concerning forehand smash skill before and after athlete used the training model.